2024
DOI: 10.3171/2023.7.jns231133
|View full text |Cite
|
Sign up to set email alerts
|

Safety and effectiveness of stent-assisted coiling with adjunctive techniques in ruptured acute aneurysms: a propensity score–matched cohort study

Ziwei Chen,
Yanhong Xin,
Liang Zou
et al.

Abstract: OBJECTIVE The use of stent-assisted coiling (SAC) in acute subarachnoid hemorrhage cases is associated with higher incidence rates of bleeding and ischemic complications. The aim of this study was to evaluate the safety and efficacy of the SAC technique in the treatment of ruptured intracranial aneurysms (RIAs). METHODS A retrospective analysis was conducted on patients with RIAs treated with SAC or coiling alone (CA). Univariate analysis compared clinical information between the two groups. Propensity score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Recently, a retrospective analysis of patients with acute wide-necked ruptured intracranial aneurysms treated with endovascular therapy revealed that patients treated with SAC achieved a higher rate of complete occlusion, a lower recurrence rate, and a greater incidence of procedure-related complications than did those treated with CA. However, the occurrence of these complications was low and comparable [ 40 ]. These outcomes are consistent with the results of our study.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a retrospective analysis of patients with acute wide-necked ruptured intracranial aneurysms treated with endovascular therapy revealed that patients treated with SAC achieved a higher rate of complete occlusion, a lower recurrence rate, and a greater incidence of procedure-related complications than did those treated with CA. However, the occurrence of these complications was low and comparable [ 40 ]. These outcomes are consistent with the results of our study.…”
Section: Discussionmentioning
confidence: 99%